Thinking as a Form of Manifestation of Social Relevance - Muminova Zarifa Odilovna (Peerian Journals Publishing, 2022)
The article analyses the functional significance of the phenomenon of thinking in the process of socialization and carries out a synergetic analysis of the role of thinking in the process of social relevance person. The article explores the issues of correct formation of peoples socio-psychological orientations and analyses the problem of correspondence of information perceived by the consciousness with the existing system of knowledge.
Keywords: thinking; socialization of person; social relevance